Концепція трагедійного в п’єсі Володимира Виниченка «Пророк» - Бойкарова, Л.Р. (Культура народов Причерноморья, 2014)
У статті розглядається концепція трагедійного у п’єсi Володимира Винниченка «Пророк».
Трагедійність цієї загадкової п’єси полягає у руйнації ілюзій, у нездатності співвіднести власні
можливості з намірами та передбачити наслідки своїх дій. Найголовніша лінія в п’єсі – випробування
пророка: він Бог чи людина. Володимир Винниченко, перейнятий ідеєю перевірки людини в
екстремальних умовах, ставить і пророка Амара в ситуації крайньої напруги, коли неминуче має
виявитися його сутність. Людина взяла на себе обов’язок пророка, щоб зробити життя краще, щоб
люди переосмислили своє мирське. Але пророку не вистачило самої віри в те, що він робить. Амар – це
глибоко–трагічна постать, духовні пошуки якої завершуються повним крахом і втратою ілюзій Відтак
пророк виявляється неспроможним виконати свою місію. П’єса перейнята драматичними напруженими
роздумами драматурга над величчю й малістю світу й людини, що спонукає нас до відчуття таїни,
правди й брехні, непримиренності різних рівнів свідомості. В статье рассматривается концепция трагедийного в пьесе Владимира Винниченко
«Пророк». Трагедийность этой загадочной пьесы заключается в разрушении иллюзий, в неспособности
соотнести собственные возможности намерениями и предусмотреть последствия своих действий.
Самая главная линия в пьесе – испытание пророка: он Бог или человек. Владимир Винниченко,
преисполнен идеей проверки человека в экстремальных условиях, ставит и пророка Амара в ситуации
крайнего напряжения, когда неминуемо должна оказаться его сущность. Человек взял на себя труд
пророка, чтобы сделать жизнь лучше, чтобы люди переосмыслили свое мирское. Но пророку не хватило
самой веры в то, что он делает. Амар – это глубоко трагическая фигура, духовные поиски которой
завершаются полным крахом и потерей иллюзий. Следовательно пророк оказывается несостоятельным
выполнить свою миссию. Пьеса проникнута драматическими напряженными размышлениями
драматурга над величием и малостью мира и человека, который побуждает нас к ощущению
таинственности, правде и лжи, непримиримости разных уровней сознания. Conception of tragic in play by Volodymyr Vynnychenko «Prophet» is examined in the article. The
tragicalness of this enigmatic play consists in destruction of illusions, in inability to correlate own possibilities
intentions and to foresee the consequences of the actions.
The most important line in a play is a test of prophet: he is God or man. V. Vynnychenko, adopted the idea of
verification of man in extreme terms, puts and prophet Amara in the situation of extreme tension, when his
essence must appear unavoidable. A man took the trouble prophet, to do life better, that people review the
mundane. But a prophet did not have a faith in that he does. Amar is deeply tragic figure the spiritual searches
of which are completed a complete crash and loss of illusions. Among the tests of prophet two is more detailed in
all given: love is without anger and love to the woman. However already here we see internal divided of prophet,
which will result in future in fatal break a secret of protagonist, – a prophet did not manage to see major, did not
manage to dissociate true from erroneous, real, eternal from mortal, earthly. He allowed to hypocritical world
to eat up itself and the searches, closing eyes on reality. He did what not a single messenger must was assume, –
he was removed from the body of people.
Consequently a prophet appears helpless to execute the mission. More main all that the heart of him must not be
covered crookedness and it follows to have a strong faith a prophet in Lord. Therefore Amar, prophet, does not
execute the mission: an illusion takes in him and interferes with him to capture an own fate. A play is adopted
the dramatic tense reflections of playwright above a grandeur and trifle of the world and man, which induces us
to feeling of secret, true and lie, irreconcilability of different levels conciseness.